IMPLEMENTASI METODE PROBLEM BASED LEARNING UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA-SISWI KELAS X PADA MATA PELAJARAN KEMUHAMMADIYAHAN DI SMK MUHAMMADIYAH 1 BANDAR LAMPUNG - Purwaningsih, Yani; Sholihin, M.; Putra, Arizal Eka (Tahdzib Al-Akhlaq: Jurnal Pendidikan Islam, 2024)
The study was prepared with the goal of increasing the performance of student education at muhammadiyah 1 municipal lampung center. Based on data that Researchers found associated with the learning process in the classroom. Only 23 percent of students The CKKM value, whereas 77 % are not able to meet the value KKM. The matter may be reviewed through the results of the above assessment The master of madiyahan has not yet been able to meet KKM as stipulated.Through the method of the based learning problem, learners make learning their way through Problems with the real world to start teaching teaching activities on In class. Before students learn their lesson of madiyahan material, the remaining wi will be dealt with one problem with solving it. In that way,To solve the problem, students would have knowledge New to be learned in order to solve the problem given. According to The research being done, the correct conclusions can be drawn Applying the method of based learning problem can be an improvement The performance of learning for the muhammadiyah x school class 1 lampung town. It is Could be reviewed from the learning achievement data at the first meeting of 71 % Increase to 91 % at the second meeting. Correct that definition, suggestion What one can share is that teachers should use the correct method Based on the material to be delivered to the disciples. After the process The study is over, the teachers improve